Evidence brief: Creating an integrated innovation system to enable the adaptation and uptake of health-system innovations in Canada - Wilson, MG; Bhuiya, AR; DeMaio, P; Gauvin, François-Pierre; Moat, KA; Cura, J; Lavis, JN (My University, 2024)
A synthesis of what is known, based on the best available global and local research evidence about the problem(s) related to creating an integrated innovation system to enable the adaptation and uptake of health-system innovations in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This evidence brief was prepared to inform a stakeholder dialogue.
Keywords: integrated innovation system; health-system innovations; Canada